A Network Pharmacology-based Study on the Anti-aging Properties of Traditional Chinese Medicine Sisheng Bulao Elixir - Xing, Cencan; Zeng, Zehua; Shan, Yubang; Guo, Wenhuan; Shah, Roshan; Wang, Luna; Wang, Yan; Du, Hongwu (Combinatorial Chemistry & High Throughput Screening, 2024)
Background: Traditional Chinese Medicine (TCM) has a rich history of use in preventing senescence for millennia in China. Nonetheless, a systematic method to study the antiaging properties and the underlying molecular mechanism of TCM remains absent. Objective: The objective of this study is to decipher the anti-aging targets and mechanisms of Sisheng Bulao Elixir (SBE) using a systematic approach based on a novel aging database and network pharmacology. Methods: Bioactive compounds and target proteins in SBE were identified via the Traditional Chinese Medicine System Pharmacology (TCMSP) database. Aging-related proteins were uncovered through alignment with the Ageing Alta database. A compound-target (CT) protein network analysis highlighted key flavonoids targeting aging. Core aging-related proteins were extracted through protein-protein interaction (PPI) network analysis. Molecular docking validated binding activities between core compounds and aging-related proteins. The antioxidant activity of SBE was confirmed using an in vitro senescent cells model. Results: A total of 39 active compounds were extracted from a pool of 639 compounds in SBE. Through a matching process with the Aging Alta, 88 target proteins associated with the aging process were identified. Impressively, 80 out of these 88 proteins were found to be targeted by flavonoids. Subsequently, an analysis using CT methodology highlighted 11 top bioactive flavonoids. Notably, core aging-related proteins, including AKT1, MAPK3, TP53, VEGFA, IL6, and HSP90AA1, emerged through the PPI network analysis. Moreover, three flavonoids, namely quercetin, kaempferol, and luteolin, exhibited interactions with over 100 aging-related proteins. Molecular docking studies were conducted on these flavonoids with their shared three target proteins, namely AKT1, HSP90AA1, and IL6, to assess their binding activities. Finally, the antioxidant properties of SBE were validated using an in vitro model of senescent cells. Conclusion: This study offers novel insights into SBE's anti-aging attributes, providing evidence of its molecular mechanisms. It enhances our understanding of traditional remedies in anti-aging research.
Keywords: Sisheng bulao elixir